The Design of Web-Based Teacher Performance Data Archiving Management Application to Increase Storage Efficiency and Information Access - Ayunda Salsabila; Supratman Zakir; Mardivta Yolanda; Nova; Misrawita (BiCED Proceeding, 2024)
The management of teacher performance data archives often faces problems in storing and accessing data quickly and accurately. To improve data access and storage, this study designed a web-based teacher performance data archive management application. Requirements analysis, system design, implementation, and evaluation are part of the application development process using the research and development (R&D) method. The system uses PHP programming language and MySQL database, and its main features are digital archive management, quick data search, and performance report generation. Test results show that the application ensures data security and accuracy while reducing data management time by 50% compared to manual methods. Application testing showed a validity result of 0.858, which falls into the valid category, as well as a practicality rate of 87%, indicating that this application is easy for teachers to use. In addition, the effectiveness test showed a value of 0.89, indicating that this application is very effective in improving the archive management process. It is hoped that the implementation of this application will assist educational institutions in improving the efficiency of archive management and help data-based decision making.